Impact of Statin or Angiotensin Converting Enzyme Inhibitor/Angiotensin Receptor Blocker on the In-Hospital Mortality of COVID-19 Patients - Mohsen Gholinataj Jelodar; Samaneh Mirzaei; Majid Hajimaghsoudi (Research Center for Rational Use of Drugs (RCRUD), 2024)
Background: It is important to determine the risk factors that contribute to the mortality of a disease and take measures to prevent or alleviate it. In the case of COVID-19, old age, male gender, and comorbidities such as diabetes (DM) and hypertension (HTN) have been identified as potential risk factors. However, there is conflicting information on the effects of statins and ACEI/ARB in COVID-19 patients admitted to the ICU, particularly those with diabetes or hypertension. This study aims to investigate the effects of these drugs on the in-hospital prognosis of ICU COVID-19 patients, with a focus on patients with DM or HTN. Methods: During 18 months, we conducted a descriptive-analytical observational analysis on 391 patients who were admitted to the ICU. The study focused on COVID-19 patients and aimed to identify mortality risk factors by assessing their demographic, clinical, pharmaceutical, laboratory, and imaging data. We statistically analyzed the data to achieve this goal. Results: Out of 391 patients, 83 received statins and 89 received ACEI/ARBs. The research has revealed that the use of ACEI/ARBs in COVID-19 patients admitted to the ICU may increase the risk of endotracheal intubation (P<0.0001) and mortality (P<0.0001). Additionally, patients treated with these drugs are more likely to experience secondary bacterial infections (P=0.007) and venous thromboembolism events (P=0.015). The results of a recent study analyzing diabetic and hypertensive patients hospitalized in ICU showed that there is no significant difference in clinical outcomes between COVID-19 patients who used ACEI/ARB and those who did not. Our study has found that the use of statins in diabetic patients is linked to a reduction in mortality rate (0.008) and secondary bacterial infections (P=0.035) of COVID-19 patients admitted to the ICU. In multivariate logistic regression, the use of statin or ACE/ARB was not identified as the mortality prediction factor. Conclusion: Statins can help reduce mortality rates among COVID-19 patients, especially in diabetic patients, hospitalized in the ICU. So, they should be used to manage cardiovascular risk factors and lower the mortality risk. Statins and ACEI/ARB drugs were not predictors of mortality and did not decrease survival rates during ICU hospitalization.